PENGARUH PENAMBAHAN MOL BONGGOL PISANG TERHADAP KUALITAS PUPUK ORGANIK CAIR (POC) BERBASIS URINE SAPI - Zulzila Arda Arnesyia; Riyanto; Intan Galuh Bintari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Cow urine is livestock waste that contains essential nutrients and has the potential to be utilized as a raw material for liquid organic fertilizer (LOF). The addition of Local Microorganisms (MOL) derived from banana corm as a bioactivator is expected to enhance the quality of LOF through the fermentation process. This study aimed to analyze the effect of banana corm MOL addition on the physical and chemical quality of cow urine-based liquid organic fertilizer and to determine the most effective dosage. The study employed an experimental method using a Completely Randomized Design (CRD) consisting of three treatments and three replications. The treatments were P0 (5 L of cow urine without MOL), P1 (5 L of cow urine + 2.5 L of rice washing water + 50 mL of banana corm MOL), and P2 (5 L of cow urine + 2.5 L of rice washing water + 100 mL of banana corm MOL). The observed parameters included physical characteristics (color, odor, texture, and pH) and chemical characteristics (nitrogen, phosphorus, and potassium contents). The results indicated that the addition of banana corm MOL improved the characteristics of liquid organic fertilizer. The best treatment was obtained in P2, which produced a dark brown color, a stable and non-pungent fermented odor, a pH of 7.06, nitrogen content of 1.98%, phosphorus content of 1.98%, and potassium content of 2.07%. However, the analysis of variance (ANOVA) showed that the addition of banana corm MOL had no significant effect (p > 0.05) on all observed parameters. Based on these findings, the application of 100 mL of banana corm MOL is recommended as the most effective treatment because it produced superior physical and chemical characteristics of cow urine-based liquid organic fertilizer.